Analysis of Factors Influencing Internship Participant Satisfaction at IP2SIP Mojosari BSIP East Java - Fatahillah, Mohammad Roikhul; Sukma, Septi Ambar Indraningtia; Chusna, Miftachul (LPPM Universitas KH. A. Wahab Hasbullah, 2025)
This study examines key factors influencing the satisfaction of internship participants in the agricultural sector, specifically at the Agricultural Instrument Testing and Standard Application Installation (IP2SIP) in Mojosari, BSIP East Java. Internships play a crucial role in bridging academic knowledge with practical industry experience, yet systematic evaluations in agriculture remain scarce. This research aims to assess the impact of time management, work environment, and internship mentorship on intern satisfaction. Using a quantitative, descriptive-associative approach, data were collected from 30 participants through questionnaires, interviews, and observations. The findings indicate that a conducive work environment and effective mentorship significantly improve internship satisfaction, while time management has a comparatively smaller impact. These results highlight the importance of enhancing workplace conditions and mentorship programs to optimize the benefits of internships in the agricultural sector.